2010
DOI: 10.1038/jp.2010.97
|View full text |Cite
|
Sign up to set email alerts
|

Patent ductus arteriosus in the preterm infant: to treat or not to treat?

Abstract: Pharmacological and/or surgical closure of a hemodynamically significant patent ductus arteriosus (PDA) in the very preterm infant has been the standard of care over the past few decades. However, the rationale for closure of PDA has recently been challenged. In this article, the factors that have fueled the controversy of the approach to the management of PDA and the gap in our knowledge are reviewed in detail. In addition, the pros and cons of the different treatment strategies applied in clinical care are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
1
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 65 publications
3
74
1
7
Order By: Relevance
“…As in other studies the current data showed a significant association between PDA and BPD (p=0.002) (Table 4) [6,9,15,20,21,25,41,42,47,[66][67][68][69]. An almost similar risk was reported by Marshall et al in VLBW infants (BW <1500 g) [69].…”
Section: Respiratory Distress Syndrome and Patent Ductus Arteriosus Isupporting
confidence: 75%
See 4 more Smart Citations
“…As in other studies the current data showed a significant association between PDA and BPD (p=0.002) (Table 4) [6,9,15,20,21,25,41,42,47,[66][67][68][69]. An almost similar risk was reported by Marshall et al in VLBW infants (BW <1500 g) [69].…”
Section: Respiratory Distress Syndrome and Patent Ductus Arteriosus Isupporting
confidence: 75%
“…A significant PDA also affects the cerebral blood flow, mostly during diastole, a possible pathway for IVH and PVL [42,46]. A link between PDA and IVH has been reported in many studies, as in the current report where there was an increased risk for IVH in Group 1 compared to Group 2 [20,40,46,47,68] (Table 4).…”
Section: Patent Ductus Arteriosus Intraventricular Hemorrhage and Pesupporting
confidence: 64%
See 3 more Smart Citations